Characterization of the Ubiquitylating Components of the Human Malaria Parasite’s Protein Degradation Pathway - Chung, Duk-Won D. (Public Library of Science, 2012)
Ubiquitin-dependent protein degradation within malarial parasites is a burgeoning field of interest due to several encouraging reports of proteasome inhibitors that were able to confer antimalarial activity. Despite the growing interest in the Plasmodium proteasome system, relatively little investigation has been done to actually characterize the parasite degradation machinery. In this report, we provide an initial biological investigation of the ubiquitylating components of the endoplasmic reticulum-associated degradation (ERAD) system, which is a major pathway in targeting misfolded proteins from the ER to the cytosol for proteasome degradation. We are able to show that the ERAD system is essential for parasite survival and that the putative Plasmodium HRD1 (E3 ubiquitin ligase), UBC (E2 ubiquitin conjugating enzyme) and UBA1 (E1 ubiquitin activating enzyme) are able to mediate in vitro ubiquitylation. Furthermore, by using immunofluorescence, we report that Plasmodium HRD1 localizes to the ER membranes, while the Plasmodium UBC and UBA1 localize to the cytosol. In addition, our gene disruption experiments indicate that the Plasmodium HRD1 is likely essential. We have conducted an initial characterization of the ubiquitylating components of the Plasmodium ERAD system, a major pathway for protein degradation and parasite maintenance. In conjunction with promising proteasome inhibitor studies, we explore the possibility of targeting the Plasmodium ERAD system for future bottom-up drug development approaches.